Crise de confiança e liquidez bancária: evidências empíricas no mercado bancário brasileiro - Piffer, Daro Marcos (2013)
The reaction of the banking authority during a crisis is very important for the mitigation of their effects. In Brazil, during the subprime crisis in 2008, it was observed a run on some banks that led the Central Bank to authorize a special line of attracting time deposits with special guarantee called DPGE. This is an opportunity to observe the depositors reaction to a shock that is exogenous to the domestic banking system, to then to explore an exogenous deposit inflow as a result of expansion within the limits of deposits insured, with coverage of the Brazilian Deposit Insurance Fund (FGC, for its acronym in Portuguese). In addition, it was analyzed the effect of the DPGE on credit supply, whereas insured and non-insured deposits are not perfect substitutes and an increase in the supply of insured deposits should increase the supply of credit in the market as a whole. The empirical strategy used allowed to recognize the issuing banks of DPGE, separating them from other factors related to the banking fundaments (size, liquidity, asset quality and return). The database used also allowed to observe the behavior of these banks and the strategy used by them at the origin and destination of such resources. Taken together, the results are consistent with the idea that depositors ran for safety during the crisis in the so-called 'flight to quality' and return when they give the security required. It is also consistent with the theory that the imperfect substitutability of insured deposits and uninsured deposits affect the tightness of banks’ financing constraints. The result of this study shows the importance of the role of the regulator facing critical situations, as well as the effects on the market caused by the permanence of a product designed for a specific situation.